FACTORS AFFECTING USE E-LEARNING IN THE LEARNNING PROCESS AT HASANUDDIN UNIVERSITY OF MAKASSAR - Monica Sulastri; Lusiana Putri Ahmadi (Accounting Department UNUSIA, 2021)
The development of an increasingly rapid era, especially in the field of information and communication technologies has penetrated in every joint of human life, especially in the world of education. Information and communication technologies themselves can provide online learning facilities, one example is e-learning. This study aims to determine the effect of perceived ease of use, perceived usefulness, subjective norms, and self-efficacy on the use of e-learning. The object of this research is a lecturer at Hasanuddin University. This research was conducted by distributing questionnaires to the respondents and then the results of the research were analyzed using PLS. The results of this study indicate that perceived ease of use, perceived usefulness, and subjective norms have a significant effect on the use of e-learning. This study implies that lecturers feel unsure in using e learning